Conversion of the genic male sterility (GMS) system of bell pepper (Capsicum annuum L.) to cytoplasmic male sterility (CMS). Issue 2 (3rd January 2014) - Mulyantoro,; Ou, Shang‐Ling; Chen, Shu‐Yun; Liu, Szu‐Chien; Lo, Tzu‐Chuan; Wahyono, Andi; Chen, Sz‐Yun; Ku, Hsin‐Mei; Flachowsky, H.
Abstract Non‐pungent bell pepper (Capsicum annuum L.) lacks the cytoplasmic male sterility (CMS) nuclear restorer allele, Rf, and CMS cannot be employed in its F1 hybrid seed production. To demonstrate that the genic male sterility (GMS) system in non‐pungent bell pepper can be converted to the CMS male sterility system, the conversion of GMS to CMS for non‐pungent bell pepper line GC3 was conducted by introgression of S‐type cytoplasm and the Rf allele from tropical pungent donors. After morphological traits were evaluated, two lines from BC1F1 containing S‐type cytoplasm and four lines from BC2F2 containing Rf allele, phenotypically similar to GC3, were obtained and could be employed as CMS male sterile lines and restorer lines for non‐pungent bell pepper. Four molecular markers potentially linked to traits of interest were also evaluated in BC1F1 and BC1F2 populations. This is the first time that GMS has been successfully converted to CMS in bell pepper, a significant contribution for bell pepper hybrid seed production.